Martin Luther and Islam : a study in sixteenth-century polemics and apologetics - Francisco, Adam (History of Christian-Muslim relations ;, 2007)
Drawing upon an array of Martin Luther's writings while also focusing upon a few key texts, this book illuminates the reformer's thought on Islam, and thereby provides fresh insights into his place in the history of Christian-Muslim relations.